Traits and Taxonomies—Building Blocks for Understanding Diversity - Smale, Melinda; King, Amanda (International Food Policy Research Institute, 2005)
Farmers and scientists start with different perspectives about the plants they breed and manage, and their ways of ordering or classifying them, called “taxonomies.” Linking these differing perspectives poses a challenge in applied research about on-farm management of crop genetic resources.